SELF-CONFIDENCE AMONG SECONDARY SCHOOL STUDENTS IN RELATION TO THEIR ACHIEVEMENT MOTIVATION (International Journal of Food and Nutritional Sciences, 2022)
The purpose of this study is to analyze the issue of Self-Confidence and its relationship with achievement motivation among secondary school students. The researcher has taken a sample 600 secondary school students. Random sampling technique is used in this study , Self-Confidence test by Dr.(Miss) Rekha Gupta (2011) and Achievement Motivation Scale by Deo and Mohan (2018) is used as tool. We found that there is a positive correlation between Self-Confidence and Achievement Motivation.